THE USE OF PAUSES, OVERLAPS, AND BACKCHANNELS IN POLITICAL CONVERSATIONS ON NAJWA SHIHAB'S YOUTUBE CHANNEL: PRAGMATICS ANALYSIS - Waruwu, Nurwian; Manurung, Lastri Wahyuni; Sidabutar, Usman (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study aims to analyze the use of pauses, overlaps, and backchanneling in political conversations on Najwa Shihab’s YouTube channel, specifically between Najwa and Ahok, using Yule’s (1996) Pragmatics theory. The research method is a descriptive qualitative method with a conversation analysis approach. Data were collected through conversation transcripts and analyzed using conversation analysis theory. The results show that pauses are divided into short and long pauses. Short pauses occurred 6 times, typically happening when a speaker is thinking or formulating the next words, while long pauses occurred 9 times, providing space for the interlocutor to think and respond. Overlaps occurred 26 times and were categorized into three types: difficulty in conversation with an unfamiliar person occurring once, expressions of closeness and solidarity occurring twice, and interruptions occurring 23 times. These overlaps often happened when both speakers spoke simultaneously, arising from awkwardness, enthusiasm, or interruptions to present a different argument or defend a point of view. Additionally, vocal backchannels, such as “mmm,” “yes,” and “okay,” occurred 11 times, while non-vocal backchanneling, such as nodding, occurred once. Backchannels serve as short responses from the listener to indicate attention, agreement, or understanding. This study concludes that these elements play a crucial role in enriching the dynamics of political conversations on social media, enhancing interaction between speakers.